Urethral Plate Characteristics in Cases of Non-proximal Hypospadias May Not Be Associated With a Higher Risk of Complications When a Two-Stage Repair Is Applied - Marcou, Marios; Bobbe, Sarah-Magdalena; Wullich, Bernd; Hirsch-Koch, Karin (Frontiers in Pediatrics, 2022)
Purpose: To investigate whether a two-stage repair of distal- and mid-shaft hypospadias (non-proximal hypospadias) could eliminate the risk factors resulting from adverse urethral plate characteristics and eventually reduce complication rates. Methods: We retrospectively reviewed all cases of primary surgical repair of non-proximal hypospadias performed in our center between 2009 and 2018. In all cases where adverse urethral plate characteristics were found, such as meatal stenosis, a shallow urethral groove, a thick web of tissue between the native meatus and the urethral pit or in the presence of a very “thin”, skin-like distal urethra, a two-stage repair was routinely undertaken. Following a first-stage operation, urethroplasty was then performed in a second procedure three to six months later. Urethroplasty was always performed using the Thiersch-Duplay technique. Patients with a follow-up of less than 12 months were excluded from this study. Results: Over a period of ten years, 208 boys underwent primary surgical repair of non-proximal hypospadias. Eighty-nine of the 208 patients (42.8%) underwent single-stage hypospadias repair. Two-stage repair of the hypospadias was required in 119 (57.2%) of the patients. At a median follow-up of 50 months, an overall complication rate of 5.8% (n=12) was observed, with the most frequent complications being urethrocutaneous fistula (n=6, 2.9%), meatal stenosis (n=3, 1.4%) and urethral stricture (n=2, 1%). No statistically significant difference was found between the complication rates of the two groups. Conclusions: Adverse urethral plate characteristics may not play a significant role in the development of postoperative complications when a two-stage approach in the repair of non-proximal hypospadias is applied.